2019
DOI: 10.1093/jac/dkz312
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum antibiotic use in Europe: more evidence of cultural influences on prescribing behaviour

Abstract: Objectives Sociocultural factors have been hypothesized as important drivers of inappropriate antibiotic prescribing in European ambulatory care. This study sought to assess whether they can also explain the reported variation in broad-spectrum antibiotic (Br-Ab) use among EU/European Economic Area (EEA) countries. Methods Correlation and regression analysis were performed, using the bootstrap method, between Br-Ab ratios rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…This is not unique to China. A survey on 28 European countries showed that broad-spectrum antibiotic contributed to over 80% of antibiotic use in 22 countries [52].…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…This is not unique to China. A survey on 28 European countries showed that broad-spectrum antibiotic contributed to over 80% of antibiotic use in 22 countries [52].…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…This is not unique to China. A survey on 28 European countries showed that broadspectrum antibiotic contributed to over 80% of antibiotic use in 22 countries [52].…”
Section: Comparison To Other Studies 13mentioning
confidence: 99%
“…Two cultural dimensions have consistently been found to explain variations in AMC both within Europe and worldwide [5][6][7][8]13,14,16 . These are Hofstede's uncertainty avoidance index (UA) and performance-orientation versus cooperation-orientation index (POCO) [5][6][7][8]13,14,16 . Both indices are negatively associated with both the proportion of a country that is Protestant 17 and AMC [5][6][7][8]16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found a range of cultural and structural factors underpin the large variations in the consumption of fluoroquinolone and other antibiotics between European countries and globally [5][6][7][8][9][10] . The act of prescribing an antimicrobial is highly social.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation